A simple and rapid technique of template preparation for PCR - Liu, Yunyun; Chen, Jia; Cheng, Yi; Li, Yi; Li, Xinwen; Zhang, Zhengbing; Xu, Xiumei; Lin, Yufeng; Xu, Jianping; Li, Zhimin (Frontiers in Microbiology, 2022)
Many techniques have been developed for extracting DNA, but most are often complex, time-consuming, and/or expensive. In this study, we describe a simple, rapid and cost-effective technique for preparing DNA template for PCR. This technique involves 0.1M potassium hydroxide treatment at 100oC for 10min followed by centrifugation. The suspended centrifuged sediments were shown as excellent templates for PCR. Templates prepared using this technique worked for diverse microorganisms belonging to bacteria, fungi and oomycetes and their amplification efficiencies were comparable to/better than those prepared using common but relatively more complex, time-consuming, and/or expensive methods, including commercial DNA extraction kits. Furthermore, this technology is suitable for high-throughput batch processing and for amplifications of long DNA fragments. Flow cytometry and scanning electronic microscopy analyses showed that this technique generated primarily damaged cells and cell-bound DNA, not free naked DNA. This technique provides a great convenience for simple PCR template preparation.